Caesarian Section Patient Profile with Indication Absolute in Dr. M. Djamil General Hospital Padang in 2018-2020 - Primadella Fegita; Rinita Amelia; Andrely Primary (Andalas Obstetrics And Gynecology Journal, 2024)
Backgrounds : Caesarea sectio delivery must be done if the existence of medical indications and normal labor can no longer be done at prioritizing the mother and baby. Objective : To find out the profile of the Caesarean sectio patient with an absolute indication at Dr. RSUP M. Djamil Padang in 2018-2020. Methods : The scope of this research is obstetrics and gynecological science. The study was conducted in March - March 2022. The type of research is descriptive categoric. The affordable population in the study was the patient sectio caesarea with an absolute indication in Dr. RSUP M. Djamil Padang in 2018-2020 as many as 56 samples with total sampling techniques. Univariate data analysis is presented in the form of frequency distribution and data processing using the Computerized SPSS version of the IBM version 25.0. Results : The highest mother age is 20-35 years, which is 38 people (67.9%). The most maternal parity is multipara, which is 38 people (67.9%). The highest education is high school, which is 31 people (55.4%). The highest history of SC It was what had a previous SC history of 33 people (58.9%), and the most absolute medical indication was the placenta previa of 24 people (42.9%). Conclusion : The highest mother age is 20-35 years. The most mother parity is multipara. The highest education is high school. The highest history of SC is who has a previous history of SC, and the most absolute medical indication is placenta previa.